Identifikasi Sindrom Turner Menggunakan Metode Bayes Berbasis Mobile - Linda Wahyu Widianti; Suyatno Suyatno; Aulia Nurhidayati (Jurnal Informatika Universitas Pamulang, 2021)
The lack of knowledge about Turner syndrome causes low public awareness of Turner syndrome. This condition makes some people put aside efforts to prevent Turner Syndrome. From this background, this research raises the title of writing, Identification of Turner Syndrome Using Android-Based Bayes Method. This study aims to make it easier for the public to find out about Turner syndrome and the possibility of someone getting Turner syndrome. This study uses two stages, namely the first stage of data collection which consists of literature study, observation. The second stage is to design a system using the System Development Life Cycle method. This study resulted in an application of the Turner Syndrome Expert System using the Android-Based Bayes Method which can make it easier for the public to know about tuner syndrome and the possibility of someone getting Turner syndrome.